2007
DOI: 10.1562/0031-8655(2001)0730257atosmt2.0.co2
|View full text |Cite
|
Sign up to set email alerts
|

Antivascular Treatment of Solid Melanoma Tumors with Bacteriochlorophyll-serine-based Photodynamic Therapy¶

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 48 publications
(56 reference statements)
1
16
0
Order By: Relevance
“…The clearance of Tookad is very fast, with a plasma half-life in the mouse typically ,1 h (A. Scherz, personal communication). Consistent with this, in several other tissues (including tumor and skin) studied in preclinical in vivo models (32), it has been observed that the light must be applied within a short time after (or even during) drug administration. In this regard, Tookad is similar to benzoporphyrin derivative monoacid ring ''a'' (Verteporfin; QLT, Vancouver, Canada), used for age-related macular degeneration, which is also activated while in the vascular system (38).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…The clearance of Tookad is very fast, with a plasma half-life in the mouse typically ,1 h (A. Scherz, personal communication). Consistent with this, in several other tissues (including tumor and skin) studied in preclinical in vivo models (32), it has been observed that the light must be applied within a short time after (or even during) drug administration. In this regard, Tookad is similar to benzoporphyrin derivative monoacid ring ''a'' (Verteporfin; QLT, Vancouver, Canada), used for age-related macular degeneration, which is also activated while in the vascular system (38).…”
Section: Discussionsupporting
confidence: 58%
“…Hence, the observations here are directly relevant to assessing the likely clinical utility of Tookadbased PDT of prostate cancer, assuming that the response of the malignant tissue will not be less than that of normal prostate. The high vascularity of tumor tissue makes it a good target for Tookad-PDT because the effects are believed to be primarily vascular (32). Furthermore, in locally recurrent cancer after radical radiation therapy, the normal prostate tissue becomes relatively avascular (33,34), which may confer some selective sensitivity of the neovascularized tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect is more pronounced in treatment protocols that involve short light/drug intervals and/or more hydrophilic sensitizers (1 3). Differences between the response of the tumor and the normal tissue vasculature may provide the key in selecting the best treatment (14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…For technical reasons, the microvessel density could only be determined for post-PDT tumor tissue because removing a portion of the tumor before PDT would cause bleeding, interfering with the blood flow measurements. As previously already demonstrated, an accurate measure for vasculature shutdown is the change in microvessel density [10,17,19,[54][55][56][57][58][59][60][61][62].…”
Section: Resultsmentioning
confidence: 90%